Measured sodium excretion is associated with cardiovascular outcomes in non-dialysis CKD patients: results from the KNOW-CKD study - Kang, Seong Cheol; Kang, Minjung; Ryu, Hyunjin; Kim, Seonmi; Kim, Ji Hye; Kang, Eunjeong; Jeong, Yujin; Kim, Jayoun; Kim, Yong-Soo; Kim, Soo Wan; Kim, Yeong Hoon; Oh, Kook-Hwan (Frontiers in Nephrology, 2023)
Background. There are insufficient studies on the effect of dietary salt intake on cardiovascular (CV) outcomes in chronic kidney disease (CKD) patients, and there is no consensus on the sodium (Na) intake level that increases the risk of CV disease in CKD patients. Therefore, we investigated the association between dietary salt intake and CV outcomes in CKD patients.Methods. In the KoreaN cohort study for Outcome in patients with CKD (KNOW-CKD), 1,937 patients were eligible for the study, and their dietary Na intake was estimated using measured 24h urinary Na excretion. The primary outcome was a composite of CV events and/or all-cause death.The secondary outcome was a major adverse cardiac event (MACE).Results. Among 1,937 subjects, there were 205 (10.5%) events for the composite outcome and 110 (5.6%) events for MACE. Compared to the reference group (urinary Na excretion < 2.0g/day), the group with the highest measured 24h urinary Na excretion (urinary Na excretion ≥ 8.0g/day) was associated with increased risk of both the composite outcome (hazard ratio 3.29 [95% confidence interval 1.00-10.81]; P = 0.049) and MACE (hazard ratio 6.28 [95% confidence interval 1.45-27.20]; P = 0.013) in a cause-specific hazard model. Subgroup analysis also showed a pronounced association between dietary salt intake and the composite outcome in subgroups of patients with abdominal obesity, female, lower estimated glomerular filtration rate (< 60 ml/min per 1.73m 2 ), no overt proteinuria, or a lower urinary potassium-to-creatinine ratio (< 46 mmol/g).A high-salt diet is associated with CV outcomes in non-dialysis CKD patients.